THE EFFECT OF UPANAHA SWEDA AND VATARI GUGGULU IN THE MANAGEMENT OF JANUSANDHIGATA VATA (KNEE OSTEOARTHRITIS): A COMPARATIVE STUDY - Arya, *Chandramohan; Gupta, Sanjay; Shukla, G.D. (International Journal of Ayurveda and Pharma Research, 2018)
Every man derives the happiness and benefit of his life through locomotion i.e., using his joints. For the minute if he loses this power of locomotion he not only feels himself a miserable creature but also becomes a burden both of his family and society. The loss or reduction in his locomotive power is due to dysfunction of the joints causing an impediment to his movements. If not treated in time, the disease makes man disable. Sandhigata Vata is most common articular disorder. It is a type of Vata Vyadhi which mainly occurs in Vriddhavastha, due to Dhatukshaya. Sandhigata Vata can be correlated with osteoarthritis (OA) which is one such chronic, degenerative, inflammatory disease and has a great impact on the quality of the life of an individual. Different modalities of treatment have been explained in the classics to tackle the condition effectively. The present study was aimed to assess clinically the effect of Upanaha Sweda and Vatari Guggulu in the management of Janusandhigata Vata. In this study total 42 patients were divided in 2 groups. In Group A, patients were treated with only Upanaha Sweda and other group patients were treated with Upanaha Sweda and Vatari Guggulu. Results obtained were analyzed for statistical significance which shows group B in which Vatari Guggulu and Upanaha Sweda were given, was more effective in bringing relief in signs and symptoms of Janusandhigata Vata.